2007
DOI: 10.1001/archpedi.161.11.1095
|View full text |Cite
|
Sign up to set email alerts
|

Glutamine-Enriched Enteral Nutrition in Very Low-Birth-Weight Infants

Abstract: Objective: To determine the effect of glutamineenriched enteral nutrition in very low-birth-weight infants on the incidence of allergic and infectious diseases during the first year of life.Design: Follow-up study.Setting: Tertiary care hospital.Participants: All surviving infants who participated in a trial of glutamine-enriched enteral nutrition in very lowbirth-weight infants.Intervention: Enteral glutamine supplementation (L-glutamine, 0.3 g/kg per day) from 3 through 30 days of life. Main Outcome Measures… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 45 publications
0
9
0
Order By: Relevance
“…Followup of all surviving VLBW infants having received enteral preterm formula or breast milk supplemented with glutamine showed a lower risk of atopic dermatitis but no differences in incidence of bronchial hyperactivity, infections of upper respiratory, lower respiratory, urinary, or gastrointestinal tracts [108, 109], of intestinal microbiota, neurodevelopmental impairment or cerebral palsy [110]. No difference was also detected among randomized groups in intestinal (faecal) microbiota at age 1 year as analyzed by fluorescent in situ hybridization [111] or in TH1 and TH2 cytokine profiles either during the days of supplementation [91] or at 1 year of age following in vitro whole blood stimulation [112].…”
Section: Randomized Experimental and Clinical Studies Of Glutaminementioning
confidence: 99%
“…Followup of all surviving VLBW infants having received enteral preterm formula or breast milk supplemented with glutamine showed a lower risk of atopic dermatitis but no differences in incidence of bronchial hyperactivity, infections of upper respiratory, lower respiratory, urinary, or gastrointestinal tracts [108, 109], of intestinal microbiota, neurodevelopmental impairment or cerebral palsy [110]. No difference was also detected among randomized groups in intestinal (faecal) microbiota at age 1 year as analyzed by fluorescent in situ hybridization [111] or in TH1 and TH2 cytokine profiles either during the days of supplementation [91] or at 1 year of age following in vitro whole blood stimulation [112].…”
Section: Randomized Experimental and Clinical Studies Of Glutaminementioning
confidence: 99%
“…In our previous study (7), we found no effect of glutamine-enriched enteral nutrition in VLBW infants in the neonatal period on cytokine profiles in neonatal period. In the current study, we specifically addressed whether glutamine administration would positively affect the immunological process, characterized by a physiological switch from a Th 2 cytokine profile in the neonatal period into a modified Th 2 profile later in life.…”
Section: Discussionmentioning
confidence: 63%
“…Specifically, supplementation with Gln or isonitrogenous control equally decreased urinary concentrations of lactulose and increased urinary mannitol [116]. More recently, followup of all surviving participants ( n = 77) revealed that Gln-enriched EN in VLBW infants may lower the incidence of atopic dermatitis (OR [95% CI]: 0.13 [0.02–0.97]) during the first year of life but has no effect on the incidence of bronchial hyperactivity or infectious diseases [117]. Further followup of this cohort of VLBW infants ( n = 76) at 6 y of age also found a decreased risk of atopic dermatitis (adjusted OR [95% CI]: 0.23 [0.06–0.95]) and gastrointestinal infections (adjusted OR [95% CI]: 0.10 [0.01–0.93]) in the Gln-supplemented group [118].…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, the results are conflicting for other short-term clinical outcomes such as feeding tolerance [99, 100, 102, 104, 107, 111, 113], serious infections/sepsis [100, 102, 107, 111, 113], ventilator use [99, 102, 104, 107, 113], and severe neurological sequelae [111]. Few data have been reported for the effects of Gln supplementation in VLBW infants on long-term clinical outcomes such as growth at 4 months [123], allergic and infectious morbidity at 1 y [117] and 6 y [118], and neurodevelopmental outcomes at 2 y corrected age [122]. Larger well-controlled studies are needed.…”
Section: Resultsmentioning
confidence: 99%